Bifidobacterium longum Suppresses Murine Colorectal Cancer through the Modulation of oncomiRs and Tumor Suppressor miRNAs. (19th May 2019) - Fahmy, Cinderella A.; Gamal-Eldeen, Amira M.; El-Hussieny, Enas A.; Raafat, Bassem M.; Mehanna, Nayra S.; Talaat, Roba M.; Shaaban, Mohamed T.
Abstract: The modulatory role of the Bifidobacterium longum (BL), isolated from women breast milk, on some oncogenic and tumor suppressor miRNAs as well as IL-1β and IL6 targeted-miRNAs was investigated using murine colorectal cancer (CRC) induced on the top of inflammatory ulcerative colitis model. The investigation of the oncomiRs miR-21a and miR-155, which regulate IL-6 and IL-1β expression, indicated that both was depressed by BL-administration in healthy and in CRC-mice. BL-administration induced the tumor suppressor miRNAs (miR-145 and miR-15a) expression in both of the healthy and in CRC-mice. The miR-146a expression, which regulates both of IL-1β and IL-6 expression, was decreased after the BL-administration in both of the healthy and in CRC-mice. In CRC-mice, NF-Kb concentration was elevated, however this NF-Kb induction was diminished after the treatment with BL. BL highly enhanced the IL-1β and IL-6 mRNA and protein concentrations in healthy mice. The administration of BL to CRC-mice resulted in a dramatic increase in IL-1β mRNA and IL-1β concentration, which in contrast was accompanied with a decrease in the IL-6 mRNA and IL-6 concentration. BL-administration resulted in a drop in the aberrant crypt foci number in CRC-mice and increased necrosis and fibrosis of the colon cells. The modulatory influence of B. longum on microRNAs may provide an important therapeutic impact in CRC through inhibition of the proliferation, invasion, apoptosis, and cell cycle of tumor cells.